Antarctic Circumpolar Current transport and barotropic transition at Macquarie Ridge - Rintoul, SR; Sokolov, S; Williams, M; Pena-Molino, B; Rosenberg, MA; Bindoff, NL (Geophysical Research Letters, 2014)
2014. American Geophysical Union. All Rights Reserved. Theory and numerical simulations suggest that topographic interactions are central to the dynamics of the Antarctic Circumpolar Current (ACC), but few observations are available to test these ideas. We use direct velocity measurements, satellite altimetry, and an ocean state estimate to investigate the interaction of the ACC with the Macquarie Ridge. Satellite altimeter data show that the Subantarctic Front crosses the ridge through a gap immediately north of Macquarie Island. Yearlong current meter records reveal strong deep mean flow (>-0.2-m-s-1 at 3000-m) and substantial transport (52 8 106-m3-s-1) in the 50-km wide gap. The ACC becomes much more barotropic at the ridge. Acceleration of the deep jet is balanced by the ageostrophic along-gap pressure gradient, convergence of zonal momentum by the mean vertical velocity, and dissipation. The study helps explain how the ACC negotiates large topographic obstacles and highlights the role of local, nonlinear processes in the dynamical balance of the ACC. Key Points Antarctic Circumpolar Current velocity was measured at Macquarie RidgeThe current becomes more barotropic as it crosses the ridgeLocal nonlinear processes accelerate deep jet